Pneumocystis pneumonia in an immunocompetent patient developing a subacute disease course with central consolidation. (2022) - Kawame, Chiaki; Yokota, Hidehiro; Shikano, Kohei; Kasai, Hajime; Suzuki, Masaki; Abe, Mitsuhiro; Kishimoto, Takashi; Ikeda, Jun-ichiro; Sakao, Seiichiro; Suzuki, Takuji
Abstract: Pneumocystis pneumonia (PCP) typically occurs in immunocompromised individuals and rarely presents in immunocompetent individuals. A 55-year-old man was referred to our hospital with cough and anorexia that persisted for 2 months. Chest computed tomography revealed bilateral central consolidation. He was diagnosed with PCP via bronchoscopy. His symptoms and imaging findings improved with the administration of only trimethoprim and sulfamethoxazole. Although he had non-alcoholic fatty liver disease, there were no other complications that could potentially cause immunodeficiency. It should be noted that PCP in immunocompetent individuals can have a subacute disease course presenting with bilateral central consolidation.